Analisis Keterlibatan Uni Emirat Arab dalam Perang Saudara Sudan Tahun 2023 - Siburian, Nathanael; Indrawati, Indrawati (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to analyze the involvement of the United Arab Emirates (UAE) in the Sudanese Civil War in 2023. It aims to explore the strategic motivations behind the UAE's actions, the extent of its influence in the conflict, and the impact of its involvement on the political, security, economic, military, and humanitarian dimensions of the war. Methodology: This study uses a qualitative approach to analyze the United Arab Emirates' (UAE) involvement in the 2023 Sudanese Civil War. Secondary data is collected through a comprehensive literature review, utilizing academic sources, reports from international organizations, credible news outlets, and official documents. Results: The United Arab Emirates (UAE) has utilized illegal gold trade as one of the means to strengthen its position in the conflict and fund military operations. Diplomatically, the UAE has leveraged political power and international relations to influence Sudan's policies and mediate peace processes that benefit its interests. Limitations: The limitations of this study include the reliance on secondary data sources, which may present biases or incomplete information. Additionally, the dynamic and evolving nature of the Sudanese Civil War in 2023 means that new developments may not be fully captured in this analysis. Contribution: This study contributes to the understanding of the United Arab Emirates' strategic involvement in the Sudanese Civil War by analyzing its political, military, and economic influence. It offers new insights into how UAE utilizes geopolitical leverage, including gold trade and diplomatic efforts, to advance its regional interests and strengthen its position in the Middle East.